2006
DOI: 10.1002/rcs.115
|View full text |Cite
|
Sign up to set email alerts
|

Robotic applications in abdominal surgery: their limitations and future developments

Abstract: Background In the past 20 years, the technical aspects of abdominal surgery have changed dramatically. Operations are now routinely performed by laparoscopic techniques utilizing small abdominal incisions, with less patient discomfort, earlier recovery, improved cosmesis, and in many cases reduced economic burden on the healthcare provider. These benefits have largely been seen in the application of laparoscopic techniques to relatively straightforward procedures. It is not clear whether the same benefits carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
(20 reference statements)
0
29
0
2
Order By: Relevance
“…In general surgery, it is used in urological endoscopy [7], digestive [8], and gynecological [9]. The most used are the da Vinci® robot and Free-Hand®.…”
Section: Discussionmentioning
confidence: 99%
“…In general surgery, it is used in urological endoscopy [7], digestive [8], and gynecological [9]. The most used are the da Vinci® robot and Free-Hand®.…”
Section: Discussionmentioning
confidence: 99%
“…The robotic system allows the surgeon to perform more sophisticated procedures, whereas classical gastrointestinal procedures can be performed safely. The development of mini robots and augmented reality techniques will boost robotic surgery in the future [9,16]. We have found that colon and rectum resections, anti-reXux surgery, and obesity surgery were safe and eYcacious for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Das stabile Kamerabild und die hohe Präzision in der Nachführung werden nicht nur mit den erwähnten hohen Investitionskosten bei den Geräten der ersten Generation, sondern auch mit einer deutlich verlängerten Operationszeit und aufwendigen Steuerungsmanövern erkauft [12,13]. Als weitere Aspekte, die gegen den Einsatz von Telemanipulatoren sprechen, werden der große Platzbedarf, die eingeschränkte Ausbildungsmöglich-keit des chirurgischen Nachwuchses und die mangelnde Flexibilität genannt [12,13,14,15].…”
Section: )unclassified